Composition of purposes and methods of guidance in Umayyad Body Experiment Poems - سليطين وفيق; زهيره بثينة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research to be carried out is to demonstrate the link between the minor units of the poem on which the poem is based in the Umayyad Body experiment to serve the main purpose, the external construction system of the traditional poem is to be found in our ancient poetic heritage, as a set of sub-units, brought together by an intellectual and emotional link within a coherent whole unit, so the scene of the initiation and what it contains in terms of poem for lover or leaving lover is not far from the psychological vision that dominates the discourse of the wasteland that the poet may interrupt during his journey, along with the necessity for these two purposes, the initiation and the journey, to have the semantic thread that connects them to the main purpose of the poem, because the integrated poetic text is what has a tight connection between its themes, leading to each other, contributing in taste and influence on the one hand, and to participate and respond on the other hand. The purposes paving the way for the main purpose of the poem in the old traditional construction are no less important than the goal to which that poem is directed, but rather they must introduce it, in order to make an impact on the recipient’s soul, and get him to respond to what the poet desires of his artistic work.